Comparative effectiveness and safety of interventions for acute diarrhoea and gastroenteritis in children: A systematic review and network meta-analysis. (2018)
ABSTRACT: Background Many interventions have shown effectiveness in reducing the duration of acute diarrhea and gastroenteritis (ADG) in children. Yet, there is lack of comparative efficacy of interventions that seem to be better than placebo among which, the clinicians must choose. Our aim was to determine the comparative effectiveness and safety of the pharmacological and nutritional interventions for reducing the duration of ADG in children.